Constructing motherhood in body politics perspective - Qadri, Prof.Dr.Chinwar Qadri (Sulaimani Journal for Humanities, 2026)
Motherhood is seen as a natural symbol of life, love, peace, language, etc. But motherhood is not an ideologically neutral individual role in society. Motherhood is a multifaceted and complex experience that individuals embody and is at the same time a symbol of a social institution. This social institution is embedded in the cultural, economic and legal systems. The analysis of motherhood is not only about the construction of gender stereotypes and normative routines. He touches on the complex and realistic issues of communications, the service economy and continuous care. Therefore, examining motherhood as a symbol of the space of relationships and economics is important for understanding the formation of gender scenarios, as well as for understanding how to maintain oppression based on gender and class. Motherhood in Kurdistan is both a place of physical weakness and oppression, and at the same time a place of resistance, which gives women a political voice This article uses the example of motherhood as an anchor point to demonstrate the psychopolitical dimensions of “body politics”. Through this perspective, the body is seen as a result of historical change and as an effect of social practice. The body is analyzed in terms of discourse, materiality and production. The body appears as the site of social order in political conflicts and decolonization. In debates about modern gender regulators, the body is reflected as a boundary marker for difference in regional and global relations of inequality.